2020
DOI: 10.1002/brb3.1821
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary results of posterior contralateral cervical 7 nerve transposition in the treatment of upper limb plegia after a stroke

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Surgical advancements in contralateral C7 nerve transfer have progressed through anatomical research, favoring the prespinal route optimized by MRI guidance for its shorter regeneration path and avoidance of nerve grafting 44 , 73 . While a posterior spinal route could potentially reduce regeneration distance, it is less commonly used due to the risk of greater trauma, underscoring the preference for the prespinal approach in clinical practice 47 , 49 , 50 , 74 , 75 . As more patients undergo contralateral C7 nerve transfer, unexpected benefits are observed.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical advancements in contralateral C7 nerve transfer have progressed through anatomical research, favoring the prespinal route optimized by MRI guidance for its shorter regeneration path and avoidance of nerve grafting 44 , 73 . While a posterior spinal route could potentially reduce regeneration distance, it is less commonly used due to the risk of greater trauma, underscoring the preference for the prespinal approach in clinical practice 47 , 49 , 50 , 74 , 75 . As more patients undergo contralateral C7 nerve transfer, unexpected benefits are observed.…”
Section: Discussionmentioning
confidence: 99%
“…One year after the procedure, the distal end of the upper limb was progressively innervated. Guan et al ( 33 ), observed that the average recovery period for motor function following contralateral C7 nerve anastomosis was more than 1 year. After C7 nerve anastomosis, progressively support the damaged limb’s various segments (e.g., elbow, forearm, wrist, etc.).…”
Section: Discussionmentioning
confidence: 99%
“…To resolve the above limitations, Guan and colleagues developed a modified postspinal approach, thereby leading to lower spastic and better sensory function by short-term follow-up after operation. 24,25 In 2019, Jiang et al 26 were the first to describe a posterior intradural approach in their cadaver feasibility study.…”
Section: Discussionmentioning
confidence: 99%
“…However, the long distances between the donor and recipient nerves increase the difficulty of surgery, significantly prolongs the operative time, and pose a high operative risk. To resolve the above limitations, Guan and colleagues developed a modified postspinal approach, thereby leading to lower spastic and better sensory function by short-term follow-up after operation 24,25. In 2019, Jiang et al 26 were the first to describe a posterior intradural approach in their cadaver feasibility study.…”
Section: Discussionmentioning
confidence: 99%